2015
DOI: 10.1177/0256090915611773
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Price Behaviour around Open Market Stock Repurchase Announcements in India

Abstract: Executive Summary This article examines the impact of open market share repurchase announcements on stock returns in the Bombay Stock Exchange (BSE). The main objective is to examine whether share repurchase announcements under the open market route have any significant impact on the returns of the stocks traded in the BSE. The article covers the period from 2009 to 2013. For sample selection, two criteria were used: first, the firm should have been listed in the BSE for at least 28 trading days before the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 20 publications
0
8
0
1
Order By: Relevance
“…Italy Lee et al (2010) 1.93% (−1, +1) 51 1990-2005 India Bhargava and Agrawal (2015) 1.00% (−1, +1) 42 2010-2014 Chatterjee and Dutta (2015) 1.81% (−1, +1) 95 2009-2013 Japan Zhang (2002) 6.00% (−1, +2) 39 1995-1999 Hatakeda and Isagawa (2004) 2.43% (−1, +1) 452 1995-1998 Korea Jung, Lee, and Thornton (2005) United Kingdom Rau and Vermaelen (2002) 1.10% (−5, +5) 246 1985-2000 Oswald and Young (2004) 1.40% (−1, +1) 266 1995-2000 Lee et al (2010) 0.80% (−1, +1) 126 1990-2005 Crawford and Wang (2012) 1.33% (−2, +2) 468 1999-2004 Andriosopoulos and Lasfer (2015) 1.68% (−1, +1) 513 [1997][1998][1999][2000][2001][2002][2003][2004][2005][2006] (continued on next page) returns, two report significant negative excess returns, and the remaining five report insignificant long-term returns. The lack of consistency may well be a result of small sample sizes, different periods and investment horizons, different methodologies to estimate expected returns, and the fact that some studies center on actual repurchases rather than buyback authorization announcements.…”
Section: Germanymentioning
confidence: 99%
See 1 more Smart Citation
“…Italy Lee et al (2010) 1.93% (−1, +1) 51 1990-2005 India Bhargava and Agrawal (2015) 1.00% (−1, +1) 42 2010-2014 Chatterjee and Dutta (2015) 1.81% (−1, +1) 95 2009-2013 Japan Zhang (2002) 6.00% (−1, +2) 39 1995-1999 Hatakeda and Isagawa (2004) 2.43% (−1, +1) 452 1995-1998 Korea Jung, Lee, and Thornton (2005) United Kingdom Rau and Vermaelen (2002) 1.10% (−5, +5) 246 1985-2000 Oswald and Young (2004) 1.40% (−1, +1) 266 1995-2000 Lee et al (2010) 0.80% (−1, +1) 126 1990-2005 Crawford and Wang (2012) 1.33% (−2, +2) 468 1999-2004 Andriosopoulos and Lasfer (2015) 1.68% (−1, +1) 513 [1997][1998][1999][2000][2001][2002][2003][2004][2005][2006] (continued on next page) returns, two report significant negative excess returns, and the remaining five report insignificant long-term returns. The lack of consistency may well be a result of small sample sizes, different periods and investment horizons, different methodologies to estimate expected returns, and the fact that some studies center on actual repurchases rather than buyback authorization announcements.…”
Section: Germanymentioning
confidence: 99%
“…Italy Lee et al (2010) 1.93% (−1, +1) 1990-2005 India Bhargava and Agrawal (2015) 1.00% (−1, +1) 2010-2014 Chatterjee and Dutta (2015) 1.81% (−1, +1) 2009-2013 Japan Zhang (2002) 6.00% (−1, +2) 1995-1999 Hatakeda and Isagawa (2004) 2.43% (−1, +1) 1995-1998 Liao, Ke, and Hu (2005) 2.90% (−1, +1) 2000-2001 Wang, Lin, Fung, and Chen (2013) 1.91% (−1, +2) 3,022 2000-2010 Thailand Nittayagasetwat and Nittayagasetwat (2013) 2.82% (−1, +1)…”
Section: Germanymentioning
confidence: 99%
“…Whereas Isa and Lee (2014), in the conclusion of their study conducted for Malaysia; for the event window (+2, +20) where the post-announcement period was considered, it was indicated that the CAAR value was calculated as 1.6%. Chatterjee and Dutta (2015) for India, in the (0, +20) event window, CAAR value was found to be 0.3%. Furthermore, when the combined event windows covering the days before and after the event are examined; it was determined that the highest CAAR value was calculated in the event window (-1, +1) with a rate of 3,6%.…”
Section: Discussionmentioning
confidence: 94%
“…While Hatakeda and Isagawa (2004) reported that the negative CAAR value in the period prior to the announcement date was calculated as -4.82% for Japan, Seifert and Stehle (2005) on the other hand, have addressed the period before the announcement date as (-25, -1) for Germany and expressed that the calculated CAAR value for this period was -6.43%. Moreover, Isa and Lee (2014), Chatterjee and Dutta (2015) and Gan, Bian, Wu and Cohen (2017), for Malaysia, India and China, respectively, put forward that positive CAAR values had been calculated in the (-20, -1) event window prior to the announcement date.…”
Section: Discussionmentioning
confidence: 99%
“…Capital gain adalah keuntungan dari hasil menjual atau membeli saham berupa kelebihan nilai jual dari nila beli saham (Falani, 2013). Pembelian kembali saham diyakini menyuntikkan beberapa pengaruh ke dalam harga saham sejak harga beli kembali ditetapkan pada tingkat yang lebih tinggi dari harga pasar yang berlaku, dengan demikian dianggap sebagai langkah penting untuk menyelamatkan pasar saham (Chatterjee, 2015).…”
Section: Sahamunclassified